Organizational aspects of accessibility of medical and pharmaceutical care for hypertensive disease in Ukraine - Sokol, K.; Kupina, O.; Olkhovska, A. (My University, 2025)
In today’s conditions, one of the leading places in the economically developed countries of the world is occupied by cardiovascular diseases, which remain the leading global public health problem. A significant position among these diseases is occupied by hypertension, which can lead to serious cardiovascular complications, and is one of the main causes of mortality of the population of the whole world, including the population of Ukraine.
Keywords: cardiovascular diseases; medical and pharmaceutical care; hypertensive disease; 2026а/2025